The Effect of Compensation and Attendance Digitalization on Employee Work Discipline at Advent Hospital Bandar Lampung: A Study on the Impact of Compensation and Attendance Systems on Employee Discipline - Oktavianto, Dentar; Susanti, Mila; Hutabarat, Francis M (Fakultas Ekonomi Universitas Advent Indonesia, 2025)
This study aims to analyze and find out how compensation, digitization of attendance and employee work discipline at Adventist Hospital Bandar Lampung, as well as to determine the influence between compensation and digitization of attendance on employee work discipline. The determination of the sample uses purposive sampling with quantitative data to describe the state of the respondents and also describe the research variables through the data analysis procedure process. The population of this study is employees of Bandar Lampung Adventist Hospital and the number of samples is 64 non-medical employee staff. The results obtained from this study show that compensation has a positive and significant influence on employee work discipline with a t-value of 2.661 and a significant 0.009 (< 0.05). Likewise, the digitization of attendance has a positive and significant influence on the level of employee work discipline, with a calculated t-value of 4.718 and a significance of 0.000 (< 0.05). The two independent variables simultaneously affect the work discipline of employees at Bandar Lampung Adventist Hospital.